PERAN NOTARIS DAN PEJABAT PEMBUAT AKTA TANAH (PPAT) SEBAGAI PEJABAT PEMBUAT AKTA IKRAR WAKAF (PPAIW) DALAM PENDAFTARAN TANAH WAKAF UNTUK MEWUJUDKAN KEMASLAHATAN UMUM - Abdullah Amirudin; Akhmad Khisni (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2017)
Wakaf is one manifestation of love to Allah SWT, seeking ridho 'by donating some of their possessions with the best treasure. Wakaf plays an important role in economic development so as to realize the benefit for all ummah. In practice there are still many of the wakif who have memakafkan some of his property and has been submitted to nadzir, but not yet on the list so that the waqf objects are not teradministrasi well and kebaradaanya still many who have not known its existence.Unregistered wakaf land has caused many problems in the community, such as the cancellation of wakaf land by the heirs as well as the exchange of wakaf land due to the development of many sectors both industrial expansion and construction of public places such as toll road development. The role of a notary publicly acting as an official of the land deed as the official of the deed of pledge of waqf in the registration of wakaf land lies in the making of the pledge of wakaf pledge, as the basis for registration of wakaf land to the national land agency. And the making of deed of exchange of bolsters and release of right to execution of land exchange of wakaf land, so that become base of perfect proof for public benefit. Keywords: notary, wakaf, deed.